A highly efficient melamine/red phosphorus flame retardant for polyurethane‐based foams. Issue 9 (19th December 2022) - Lu, Wei; Zeng, Zhipeng; He, Zhenglong; Liang, Yuntao; Sun, Yong; Song, Shuanglin; Wang, Lili; Liu, Ruling
Abstract: A highly dispersed melamine/red phosphorus (MA/RP) composite flame retardant was prepared by means of simple mechanical grinding. After co‐thermal pretreatment with polyether polyol (PPG‐2000) at 135°C, organic–inorganic hybrid foams (MA/RP/HF) containing MA/RP flame retardant were prepared by the one‐step method using main raw materials such as polyisocyanate and sodium silicate. When 0.5 wt% MA/RP with the mass ratio of 1:5 is added, MA can realize the uniform dispersion of RP in the substrate and enhance its flame retardancy, and the obtained MA/RP/HF presents uniform and closed pores and excellent basic properties. The TG results reveal that MA/RP/HF shows good thermal stability and the corresponding char residual rate reaches 37.9% at 800°C. The flame retardant test results prove that MA/RP/HF is capable of passing the V‐0 grade, with the LOI value being 26.8%. According to the cone calorimeter analysis, its peak heat release rate and total heat release decrease by 30.1% and 51.7% compared with those of rigid polyurethane‐based foam and by 40.1% and 30.0% compared with those of pure HF, respectively. Finally, the synergistic flame retardancy mechanism of MA and RP on polyurethane‐based foam was discussed. Abstract :